Comparison of three fixation techniques for arcuate fractures. Issue 2 (February 2020) - Hodax, Jonathan D.; Cohen, Brian H.; DeFroda, Steven F.; Sobel, Andrew D.; Fadale, Paul D.
Highlights: Biomechanical analysis of three types of arcuate fragment fixation revealed robust fixation among all methods. Fixation may depend size of bony fragment and whether or not the injury is a bony or soft tissue injury. Fixation may also depend on fibula anatomy and size and should be individualized. Abstract: Purpose: Proximal fibula avulsion fractures, or "arcuate fractures", are an often discussed but poorly defined injury pattern which represent a destabilizing injury to the posterolateral corner of the knee. Historical and recent literature discussing reconstruction and repair techniques exist, but there has been little biomechanical evaluation of repair techniques. The purpose of this study was to evaluate the strength of three type of fixation techniques for arcuate fractures: bone tunnels, a screw and washer, and a novel suture anchor technique. Methods: A laboratory model of the arcuate fracture pattern was developed. This was used to create an arcuate fracture in 24 cadaveric specimens. Knees were randomized into fixation with either suture tunnel (ST), screw and washer (SW), or suture anchor (SA) repair. A previously published model for inducing varus stress was applied and a MTS testing system was used to assess fixation ultimate and yield strength. Results: Fibular fracture occurred during the fixation of one specimen from the ST group and one from the SA group. Analysis of the remaining 22 specimens revealed a mean ultimate strength of 2422.48 N for the ST group, 2271.78 for SW, and 3041.66 for SA ( p = 0.390). Yield strengths were 2065.28 for ST, 1882.43 for SW, and 2871.92 for SA ( p = 0.224). Analyses of stiffness and total energy applied were not statistically different ( p = 0.111 and 0.601, respectively). Conclusion: Biomechanical analysis of three types of arcuate fragment fixation revealed robust fixation among all methods, supporting surgeon preference for fixation. Fixation may depend on the size of bony fragment and whether or not the injury is a bony or soft tissue injury.